Mercury anomalies and the timing of biotic recovery following the end-Triassic mass extinction - Alyson M. Thibodeau (Nature Portfolio, 2016)
The association between Central Atlantic Magmatic Province (CAMP) eruption volatiles and the end-Triassic mass extinction remains ambiguous. Here, the authors present mercury and palaeontological evidence from the same archive and show that significant biotic recovery did not begin until CAMP eruptions ceased.